2004
DOI: 10.1038/sj.onc.1208082
|View full text |Cite
|
Sign up to set email alerts
|

An HSP90-mimic peptide revealed by fingerprinting the pool of antibodies from ovarian cancer patients

Abstract: To gain insight into the mechanisms of molecular recognition and humoral immune response in ovarian cancer, we used fingerprinting, a phage display-based combinatorial selection to isolate peptide ligands to tumor-related antibodies present in ascites from patients with advanced disease. First, we have isolated a consensus motif (sequence CVPELGHEC) in 86% of the peptides screened; this enriched motif was selected from a total of 10(8)-10(9) unique random sequences present in the library. Next, we identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 17 publications
0
40
0
1
Order By: Relevance
“…Fingerprinting of enriched serum antibodies with phage display offers a more direct combinatorial screening for antibody epitopes and has identified numerous biologically relevant antigens (7)(8)(9)(10)(11)(12). Moreover, studies from other laboratories have indicated clinical relevance in cancer diagnostics for antibodies against molecules such as osteopontin (20,21), isoprostanes (22), and CXCL13 (23), among others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fingerprinting of enriched serum antibodies with phage display offers a more direct combinatorial screening for antibody epitopes and has identified numerous biologically relevant antigens (7)(8)(9)(10)(11)(12). Moreover, studies from other laboratories have indicated clinical relevance in cancer diagnostics for antibodies against molecules such as osteopontin (20,21), isoprostanes (22), and CXCL13 (23), among others.…”
Section: Discussionmentioning
confidence: 99%
“…antigenicity of a tumor and may identify serum autoantibodies of diagnostic and prognostic value. We applied a phage display fingerprinting approach (7,8) on isolated antibodies from sequentially acquired serum samples from an index patient and performed three rounds of selection for each time point. Relative phage recovery was very similar from serum obtained at initial diagnosis of castrate-sensitive prostate adenocarcinoma (year 0) and serum obtained during androgen ablation treatment, in which PSA was undetectable (year 1) (Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Such a high-throughput approach proved effective in the identification of autoantibody signatures in prostate and ovarian cancer (6)(7)(8). In ongoing work, we have applied this protocol to sera from an index patient with welldocumented spontaneously regressed metastatic RCC (9), as well as to a classic experimental rat model of RCC (10), corroborating the presence of a humoral immunity against the broad repertoire of tumor vascular antigens.…”
mentioning
confidence: 79%